2015
DOI: 10.1111/apt.13143
|View full text |Cite
|
Sign up to set email alerts
|

Functional gastrointestinal disorders in 35 447 adults and their association with body mass index

Abstract: SUMMARY BackgroundFunctional gastrointestinal disorders' (FGIDs) associations with body mass index (BMI) have not been thoroughly investigated in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
79
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 61 publications
11
79
0
7
Order By: Relevance
“…There were mixed results regarding the association of IBS and obesity. There were studies that found higher IBS prevalence with increased BMI, 49,50 and waist-circumference and visceral adipose tissue. 51 Other authors cautioned regarding selection of study patients and need of a standardized assessment of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…There were mixed results regarding the association of IBS and obesity. There were studies that found higher IBS prevalence with increased BMI, 49,50 and waist-circumference and visceral adipose tissue. 51 Other authors cautioned regarding selection of study patients and need of a standardized assessment of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Le Pluart et al 15 found that IBS and functional constipation frequently coexist in subjects suffering from FD. Our result was consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent large scale study showed that high BMI had a significant association with increased risk of FD in females. 15 Abdominal adipose tissue consists of two functionally and anatomically distinct types of fat, visceral, and subcutaneous adipose tissue. Visceral adipose tissue not only has metabolic effects, 16 but may also increase intra-abdominal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The present study underlines the importance of the enrollment source to define the association between BMI and FGIDs. In fact, independently of the country of origin, previous studies associated BMI and organic or functional digestive disorders in cohort patients from different types of enrollment: functional disease recruitment [28], weight loss programs [29], bariatric surgery [20], endoscopic evaluation [27,30], or epidemiological studies [31,32]. In addition, some studies could include control groups [33] but did not separate obese patients according to their BMI [34].…”
Section: Discussionmentioning
confidence: 99%